The UNESCO Environmental Corridor of Extremadura: Tourism and Governance as Tools for Social Sustainability - Rocío Blanco-Gregory; Marcelo Sánchez-Oro Sánchez; Margarita Calleja-Aldana (Societies)
Tourism governance evaluates the participation of stakeholders in planning and development decisions within a territory. Understanding who these stakeholders are and their involvement is crucial, as tourism impacts social, economic, and cultural spaces, requiring equitable distribution of its costs and benefits to ensure sustainability. This study focuses on the UNESCO Environmental Corridor of Extremadura, using data from the Tourism Observatory of Extremadura and visitor surveys to define its tourist scope. A literature review identified dimensions and variables of tourism governance, leading to the design of questionnaires and evaluation scales, as well as the identification of stakeholders based on existing research. Results reveal variability in tourism governance across territories, with a notable lack of management concerning gender and functional diversity. While aligning with existing literature on the underdevelopment of shared governance policies, the study highlights progress in stakeholder participation strategies, particularly in territories with UNESCO designations. The UEC territories stand out for their strategic tourism development plans, stakeholder consultation, sector coordination, and diverse participatory decision-making mechanisms.